2022
DOI: 10.1002/ptr.7555
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of Eleutherococcus senticosus on the neurological disorders

Abstract: Eleutherococcus senticosus is a medicinal plant widely used in traditional medicine and edible remedies with effects on anti-fatigue, sleep improvement, and memory enhancement. Recently, the application of E. senticosus to neurological disorders has been a focus. However, its overall pharmacological effect on neural diseases and relevant mechanisms are needed in an in-depth summary. In this review, the traditional uses and the therapeutic effect of E. senticosus on the treatment of fatigue, depression, Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Acanthopanax senticosus, family Araliaceae), also known as Siberian ginseng or eleuthero, is distributed mainly in cold areas, such as southeastern Russia, northern China, Siberia, Japan, and North Korea. 1,2 Traditionally, E. senticosus is used as a classical adaptogen, a medicinal plant that increases the non-specific inter-systemic antistress effects of the organism. 3,4 As a natural herbal medicine with tonifying, sleepstrengthening, and tranquilizing effects, 5 it was recorded in the 2020 edition of the Chinese Pharmacopoeia and the 14th edition of the Russian Pharmacopoeia, 4,6 and it was approved by the European Medicines Agency (EMA) in 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acanthopanax senticosus, family Araliaceae), also known as Siberian ginseng or eleuthero, is distributed mainly in cold areas, such as southeastern Russia, northern China, Siberia, Japan, and North Korea. 1,2 Traditionally, E. senticosus is used as a classical adaptogen, a medicinal plant that increases the non-specific inter-systemic antistress effects of the organism. 3,4 As a natural herbal medicine with tonifying, sleepstrengthening, and tranquilizing effects, 5 it was recorded in the 2020 edition of the Chinese Pharmacopoeia and the 14th edition of the Russian Pharmacopoeia, 4,6 and it was approved by the European Medicines Agency (EMA) in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Maxim. (synonymous with Acanthopanax senticosus , family Araliaceae), also known as Siberian ginseng or eleuthero, is distributed mainly in cold areas, such as southeastern Russia, northern China, Siberia, Japan, and North Korea 1,2 . Traditionally, E. senticosus is used as a classical adaptogen, a medicinal plant that increases the non‐specific inter‐systemic antistress effects of the organism 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ginsenosides Rg1, Rg5, Re, and Rb1 from Ginseng had been demonstrated with significant anti‐AD effects (Razgonova et al, 2019). Additionally, eleutherosides C3, M, and B from Siberian ginseng have the ability to cross the blood–brain barrier (BBB) and improve memory impairment in AD mouse models (Li et al, 2022). Notoginsenoside R1 (NR1), a major constituent of plant Panax notoginseng , exhibits anti‐inflammatory and antioxidative properties and can improve learning and memory functions and redressed neuronal hyperexcitability in AD model by modulating sodium channels (Yan et al, 2014).…”
Section: Ts and Neuroprotective Activitymentioning
confidence: 99%
“…Related research showed ( 8 – 10 ) that traditional Chinese medicine with multiple components, targets, and pathways can treat AD by improving neurocholine function, reducing inflammatory response, and resisting oxidative stress. Acanthopanax senticosus (AS) is a Wujiaceae plant that can improve sleep, enhance memory, and reduce fatigue ( 11 ). Relevant experimental studies have shown that AS extract can significantly enhance mice’s object recognition memory ( 12 ); EEAK (ethanol extract of AS) can improve cognitive dysfunction caused by cholinergic blockade and improve the performance of mice in Y-maze and novel object recognition experiments ( 13 ).…”
Section: Introductionmentioning
confidence: 99%